Experimental Investigation on the Machinability Improvement in Magnetic-Field-Assisted Turning of Single-Crystal Copper - Xian Wu; Yu Zhou; Congfu Fang; Laifa Zhu; Feng Jiang; Ke Sun; Yuan Li; Yiyang Lin (Micromachines, 2022)
The single-point diamond-turning operation is a commonly used method for ultra-precision machining of various non-ferrous materials. In this paper, a magnetic field was introduced into a single-point diamond-turning system, and magnetic-field-assisted turning experiments were carried out. The results revealed that the magnetic field affects the metal-cutting process in the form of the cutting force, chip morphology, and surface quality. Compared with traditional turning, magnetic-field assisted turning increases the cutting force by 1.6 times, because of the additional induced Lorentz force, and reduces the cutting-force ratio and friction coefficient on the rake surface by 16%, with the improved tribological property of the tool/chip contact-interface. The chip morphology in the magnetic-field-assisted turning shows the smaller chip-compression ratio and the continuous side-morphology. With the magnetoplasticity effect of the metal material and the friction reduction, magnetic-field-assisted turning is helpful for improving metal machinability and achieving better surface-quality.